FLAT DILATOMETER TEST FOR CHARACTERIZATION AND PREDICTING SETTLEMENTS IN A SANDY SOIL SITE - Rocha, Breno Padovezi [UNESP]; de SOUZA, Maria Clara Aparecida; Herrera, Luis Pedro Rojas [UNESP]; Giacheti, Heraldo Luiz [UNESP] (UNESP - Universidade Estadual Paulista, 2025)
When loaded, civil engineering works settle, thus making it necessary to estimate and analyze the settlements of the designed structure. To estimate these values, it is necessary to know the modulus of deformability of the soil (Es), but its determination in sandy soils is complex, as obtaining undisturbed samples in these soils is a challenging task. Therefore, in situ tests, such as the Flat Marchetti Dilatometer (DMT), are interesting tools for this purpose. This paper presents and discusses the results of four DMTs carried out on a profile of clayey fine sand located on the Unesp Experimental Research Site in Bauru. The soil type was classified based on these results and the design parameters were estimated using correlations, which were compared with reference values. The settlement was then estimated using the traditional elastic-linear approach and were compared with plate load tests (PLTs) previously carried out on at this site at 1.0, 2.0, 3.0 and 4.0 m depths. The DMT proved to be an efficient tool for characterizing the soil profile studied. It was also found that in unsaturated soils, there is a need to consider the effect of suction when interpreting in situ tests, as the mechanical behavior of unsaturated tropical soils is strongly influenced by it, affecting predictions of the soil's mechanical behavior.
ENSAIO DE DILATÔMETRO PLANO PARA CARACTERIZAÇÃO E PREVISÃO DE RECALQUES EM UM LOCAL DE SOLO ARENOSO
Keywords: Constrained modulus; DMT; Sandy soils; Settlements estimation; Site investigation